2002
DOI: 10.1021/ja017386d
|View full text |Cite
|
Sign up to set email alerts
|

The First Total Synthesis of Lipid II:  The Final Monomeric Intermediate in Bacterial Cell Wall Biosynthesis

Abstract: Bacterial peptidoglycan is composed of a network of beta-[1,4]-linked glyan strands that are cross-linked through pendant peptide chains. The final product, the murein sacculus, is a single, covalently closed macromolecule that precisely defines the size and shape of the bacterial cell. The recent increase in bacterial resistance to cell wall active agents has led to a resurgence of activity directed toward improving our understanding of the resistance mechanisms at the molecular level. The biosynthetic enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 24 publications
0
97
0
Order By: Relevance
“…Furthermore, lipid II contains a 55-carbon polyprenyl chain that renders it insoluble in water and difficult to handle in enzyme assays. To enable the study of bacterial transglycosylases, we and others (10,20,21) have established synthetic routes to natural lipid II and analogues containing truncated polyprenyl chains (10). We previously reported that compound 10, which contains a 35-carbon lipid chain, is a better substrate than natural lipid II to use for monitoring PBP1b activity in vitro (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, lipid II contains a 55-carbon polyprenyl chain that renders it insoluble in water and difficult to handle in enzyme assays. To enable the study of bacterial transglycosylases, we and others (10,20,21) have established synthetic routes to natural lipid II and analogues containing truncated polyprenyl chains (10). We previously reported that compound 10, which contains a 35-carbon lipid chain, is a better substrate than natural lipid II to use for monitoring PBP1b activity in vitro (10).…”
Section: Resultsmentioning
confidence: 99%
“…A major impediment to studying these enzymes has been that adequate supplies of lipid II cannot be obtained from natural sources. The development of synthetic approaches to make lipid II and analogues has solved the substrate problem (10,20,21), making it possible to assay inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…So far, access to Lipid II and variants was limited to groups having considerable synthetic expertise (14,16,17). We reasoned that it should be possible to produce Lipid II if membrane preparations carrying sufficient MraY and MurG activity were provided with the appropriate UDP-activated amino sugars and undecaprenyl phosphate in the presence of a suitable detergent.…”
Section: Synthesis Of Lipid II Andmentioning
confidence: 99%
“…This enables the C terminus, which consists of the knotted DE-ring system, to form pores in the phospholipid membrane, which ultimately lead to cell leakage and collapse of the vital ion gradients across the membrane. [3] Lipid II [4] is an essential precursor for cell-wall synthesis. [5] It consists of two amino sugars, N-acetyl glucosamine (GlcNAc) and N-acetyl muramic acid (MurNAc), and a pentapeptide (usually H-Ala-d-Glu(Lys-d-Ala-d-Ala-OH)-OH-) that is attached to the carboxyl moiety of MurNAc.…”
Section: Introductionmentioning
confidence: 99%
“…After completion of the reaction, DCM was removed under reduced pressure, and the residue was dissolved in EtOAc (25 mL mmol À1 ). The solution was washed with KHSO 4 (1 n, 3 25 mL), 10 % Na 2 CO 3 (3 25 mL), and brine (1 25 mL), then dried (Na 2 SO 4 ), filtrated, and evaporated in vacuo. The …”
mentioning
confidence: 99%